Método de estudio de caso como estrategia de aprendizaje para mejorar el nivel de comprensión lectora en los estudiantes del cuarto grado de primaria de la Institución Educativa Fe y Alegría n° 46 San Juan Bautista 2022 - Vásquez Rengifo, Maira (2023)
The objective of the research is to determine how the case study method as a learning strategy influences the improvement of reading comprehension in fourth grade students of the Fe y Alegría Educational Institution No. 46. San Juan Bautista 2022. Methodology applied research, quasi-experimental design. Sample consisting of. 30 students from section A experimental group and 30 students from section B control group. Results it was determined that in the Control group, the application of the case study method as a learning strategy does not significantly influence the improvement of the literal level in the students of the fourth grade session B. (p = 0.859), but in the experimental group if it significantly influences the improvement of the literal level in the students of the fourth grade session A. (p = 0.006). It was also determined that in the Control group, the application of the case study method does not significantly influence the improvement of the inferential level in the students of the fourth grade session B, (p = 0.451). But in the experimental group, the application of the case study method as a learning strategy does significantly influence the improvement of the inferential level. (p=0.000<0), likewise in the Control Group the application of the case study method, as a learning strategy does not significantly influence the improvement of the critical level, (p = 0.116>0.05).